Anatomical characteristics of macroalgal species from Bombuyanoi Island, East Bolaang Mongondow Regency, North Sulawesi - Patra, Frian; Kepel, Rene Ch.; Lumingas, Lawrence J.L.; Gerung, Grevo S.; Kondoy, Khristin F.; Sumilat, Deiske A.; Undap, Suzanne L. (AQUATIC SCIENCE & MANAGEMENT, 2021)
This research aims to study the anatomical structure of macroalgae. Sample of macroalga was collected by using Line Intercept Transect (LIT) method with sampling quadrat. Macroalgae samples were dried and separated from the roots, stems, leaves and receptacles (if present). Samples were cut transversely and longitudinally at each section and observed under binoculared microscope of Olympus CX with monitor. Based on the histology, anatomical structure of macroalgae species can be divided into two tissues from outside to inside, namely cortex and medullary cells. The cortex is composed of one layer or more. The cortex is the area between the epidermis and the central column. The medulla cells only have one layer which is the largest layer. Based on the observation result of cells type from observed spesies Eucheuma denticilatum, Gracilaria arcuata, Hydropuntia edulis, G. salicornia, Hypnea valentiae, Turbinaria deccurens, and T. ornata, it shows that cells of medulla become small toward cortex.Indonesian title:Â  Karakteristik anatomi jenis makroalga dari Pulau Bombuyanoi, Kabupaten Bolaang Mongondow Timur, Sulawesi Utara